Rawlsian Perfectionism - Wall, Steven (Journal of moral philosophy, 2013)
This paper presents and defends a Rawlsian argument for perfectionist state policies. The argument draws on Rawls’s discussion of the “Aristotelian Principle,” highlighting the complex relationship between this principle and the social bases of self-respect. The paper explains how Rawls’s discussion and endorsement of this principle has significant and unappreciated implications for his account of the human good and the state’s role in promoting it in a well-ordered society. Although Rawls explicitly rejected state perfectionism, the paper shows how his conception of justice has the resources to respond to the important criticism that it is insufficiently responsive to the claims of human excellence. Rawlsian perfectionism, in this way, strengthens Rawlsian justice by removing an important reason for rejecting it.